Eksplorasi Dinamika Pembelajaran Matematika melalui Aplikasi AI dalam Metode Teams Game Tournament: Studi Kasus di SMA Negeri 1 Bangorejo - Aditia Ilham Imas Samporno; Muhammad Hasan Asnawi (IEC: Journal of Educational Innovation, 2026)
This study explores the dynamics of mathematics learning through the integration of Artificial Intelligence (AI) applications within the Teams Game Tournament (TGT) method at SMA Negeri 1 Bangorejo. Using a qualitative case study approach, data were collected through in-depth interviews with two mathematics teachers and five students, supplemented by classroom and environmental observations. The findings reveal four specific learning dynamics: (1) a structured five-stage learning sequence that systematically operationalizes constructivist knowledge construction; (2) a categorical shift in the teacher's role from sole instructor to multi-layer facilitator; (3) student activeness driven by collective accountability to the team rather than individual obligation; and (4) differential AI functions adapted to each student's learning needs. Students' responses demonstrated five distinct profiles ranging from affective transformation and collaborative satisfaction to reflective independence and increased self-confidence. Four benefit dimensions were identified — pedagogical, cognitive, social, and metacognitive — accompanied by four categories of challenges and three adaptive strategy groups developed organically in the field. This research contributes four grounded concepts: Multi-Source ZPD, Collective Accountability, AI Psychological Safe Zone, and Organic Peer Scaffolding (OPS).